Sleep and Neurochemical Modulation by DZNep and GSK-J1: Potential Link With Histone Methylation Status - Murillo-Rodríguez, Eric; Arankowsky-Sandoval, Gloria; Barros, Jorge Aparecido; Rocha, Nuno Barbosa; Yamamoto, Tetsuya; Machado, Sérgio; Budde, Henning; Telles-Correia, Diogo; Monteiro, Diogo; Cid, Luis; Veras, André Barciela (Frontiers in Neuroscience, 2019)
Histone methylation/demethylation plays an important modulatory role in chromatin restructuring, RNA transcription and is essential for controlling a plethora of biological processes. Due to many human diseases have been related to histone methylation/demethylation, several compounds such as 3-deazaneplanocin A (DZNep) or 3-((6-(4,5-Dihydro-1H-benzo[d]azepin-3(2H)-yl)-2-(pyridin-2-yl)pyrimidin-4-yl)amino)propanoic acid; N-[2-(2-pyridinyl)-6-(1,2,4,5-tetrahydro-3H-3-benzazepin-3-yl)-4-pyrimidinyl]-β-Alanine (GSK-J1), have been designed to inhibit histone methylase or suppress histone demethylase, respectively. In the present study, we investigated the effects on the sleep-wake cycle and sleep-related neurochemical levels after systemic injections of DZNep or GSK-J1 given during the light or dark phase in rats. DZNep dose-dependently (0.1, 1.0 or 10mg/Kg, i.p.) prolonged wakefulness (W) duration while decreased slow wave sleep (SWS) and rapid eye movement sleep (REMS) time spent during the lights-on period with no changes observed in dark phase. In opposite direction, GSK-J1 (0.1, 1.0 or 10mg/Kg, i.p.) injected at the beginning of the lights-on period induced no statistical changes in W, SWS or REMS whereas if administered at darkness, we found a diminution in W and an enhancement in SWS and REMS. Finally, brain microdialysis experiments in freely moving animals were used to evaluate the effects of DZNep or GSK-J1 treatments on contents of sleep-related neurochemicals. The results showed that DZNep boosted extracellular levels of dopamine, norepinephrine, epinephrine, serotonin, adenosine and acetylcholine if injected at the beginning of the lights-on period whereas GSK-J1 exerted similar outcomes but when administered at darkness. In summary, DZNep and GSK-J1 may control the sleep-wake cycle and sleep-related neurochemicals trough histone methylation/demethylation activity.